Case Report: CMV-Associated Congenital Nephrotic Syndrome - Jacob, Anju; Habeeb, Shameer M.; Herlitz, Leal; Simkova, Eva; Shekhy, Jwan F.; Taylor, Alan; Abuhammour, Walid; Abou Tayoun, Ahmad; Bitzan, Martin (Frontiers in Pediatrics, 2020)
Background: Congenital nephrotic syndrome, historically defined by the onset of large proteinuria during the first three months of life, is a rare clinical disorder, generally with poor outcome. It is caused by pathogenic variants in genes associated with this syndrome or by fetal infections disrupting podocyte and/or glomerular basement membrane integrity. Here we describe an infant with congenital CMV infection and nephrotic syndrome that failed to respond to targeted antiviral therapy. Case and literature survey highlight the importance of the “tetrad” of clinical, virologic, histologic and genetic workup to better understand the pathogenesis of CMV-associated congenital and infantile nephrotic syndromes. Case presentation: A male infant was referred at nine weeks of life with progressive abdominal distention, scrotal edema and vomiting. Pregnancy was complicated by oligohydramnios and prematurity (34 weeks). He was found to have nephrotic syndrome and anemia, normal platelet and white blood cell count, no splenomegaly, and no syndromic features. Diagnostic workup revealed active CMV infection (positive CMV IgM/PCR in plasma) and decreased C3 and C4. Maternal anti-CMV IgG was positive, IgM negative. Kidney biopsy demonstrated focal mesangial proliferative and sclerosing glomerulonephritis with few fibrocellular crescents, interstitial T- and B-lymphocyte infiltrates, and fibrosis/tubular atrophy. Immunofluorescence was negative. Electron microscopy showed diffuse podocyte effacement, but no cytomegalic inclusions or endothelial tubuloreticular arrays. After four weeks of treatment with valganciclovir, plasma and urine CMV PCR were negative, without improvement of the proteinuria. Unfortunately, the patient succumbed to fulminant pneumococcal infection at seven months of age. Whole exome sequencing and targeted gene analysis identified a novel homozygous, pathogenic variant (2071+1G>T) in NPHS1. Literature review and discussion: The role of CMV infection in isolated congenital nephrotic syndrome and the corresponding pathological changes are still debated. A search of the literature identified only three previous reports of infants with congenital nephrotic syndrome and evidence of CMV infection, who also underwent kidney biopsy and genetic studies. Conclusion: Complete workup of congenital infections associated with nephrotic syndrome is warranted for a better understanding of their pathogenesis (“diagnostic triad” of viral, biopsy and genetic studies). Molecular testing is essential for acute and long-term prognosis and treatment plan.